The seizure recurrence rate in epileptic patients following universal health coverage - Reza Khadivi; Parastoo Golshiri; Zahra Sadeghi (Shahid Beheshti University of Medical Sciences, 2020)
Background - Identifying the risk factors for seizure recurrence in epileptic patients is necessary for making decision about treatment. The goal of this study was to assess the seizure recurrence rate in Epileptic patients after Universal Health Coverage implementation Methods - 245 epileptic patients participated in our study. All of confirmed Epileptic patients were monitored continuously every month through the study and the signs or symptoms attributed to the suspected seizure were assessed and referred to the physician for additional assessment and consultation to improve treatment compliance. In this study, the incidence of Relapse in epileptic cases and its risk factors in rural areas of Isfahan district and the effect of Universal Health Coverage was evaluated. The obtained data was analyzed by SPSS 20 software using ANOVA and Chi-square tests. Results - Out of 245 epileptic patients, 37 patients (14.8%) displayed SR that exposed a total of 80 seizure recurrence attacks (2.16 per person). Forgetting to take their medication was found as the greatest cause of seizure recurrence and lack of adherence to treatment. 23.1% of the patients reported family history of seizure. Only family history of seizure had a significant association with the frequency of recurrence. Conclusions - In such primary health delivery system that neuropsychiatric health packages were integrated, Universal Health Coverage implementation can reduce the incidence rate of seizure recurrence attack in epileptic patients.